Revolutionizing Cloud Data Security with Elliptic Curve Cryptography - V. Jainendra,; C. Yamini, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Encryption helps in transmitting sensitive data over an insecure channel without any danger of data being lost or being manipulated by some unauthorized entity. Different Encryption schemes have been applied for Data security in a different environment. Many cryptosystems worked during different eras and evolved accordingly with time. This paper mainly focuses on asymmetric encryption which is also known as Public key encryption scheme or Homomorphic encryption. However, due to large key size asymmetric encryption is mostly used for Key exchange rather than data Encryption. Nowadays, Data security is the main issue in large data centres and Cloud computing. This paper uses Elliptic Curve Cryptography to encrypt data in the cloud environment because the size of the key used in Elliptic Curve Cryptography is very small. Due to the small key size of Elliptic Curve, computational power is reduced and this results into least energy consumption. This paper shows that elliptic curve cryptography is fast and more efficient for data protection in a cloud computing environment and reduces the computational power and also increases the efficiency.
Keywords: Elliptic Curve Cryptosystem (ECC); Cloud Computing; Data security